2017
DOI: 10.3390/s17081740
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Mixed-Potential-Type (MPT) NO2 Sensor Based on An Ultra-Thin Ceramic Film

Abstract: A novel flexible mixed-potential-type (MPT) sensor was designed and fabricated for NO2 detection from 0 to 500 ppm at 200 °C. An ultra-thin Y2O3-doped ZrO2 (YSZ) ceramic film 20 µm thick was sandwiched between a heating electrode and reference/sensing electrodes. The heating electrode was fabricated by a conventional lift-off process, while the porous reference and the sensing electrodes were fabricated by a two-step patterning method using shadow masks. The sensor’s sensitivity is achieved as 58.4 mV/decade a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It indicated that the response rate rose as the Fe doping ratio increased because of the increased porosity of the SE layer, as shown in SEM images (Figure S2). Usually, the time required to reach 90% Δ U is defined as the response time ( T 90 ), and the time required to recover to 10% Δ U is defined as the recovery time ( T 10 ) . For the BiV 0.8 Fe 0.2 O δ -SE sensor, the T 90 and T 10 were 89.9 and 321.8 s, respectively, to 50 ppm of NH 3 , while the T 90 of the BiVO 4 –SE sensor was 354.1 s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicated that the response rate rose as the Fe doping ratio increased because of the increased porosity of the SE layer, as shown in SEM images (Figure S2). Usually, the time required to reach 90% Δ U is defined as the response time ( T 90 ), and the time required to recover to 10% Δ U is defined as the recovery time ( T 10 ) . For the BiV 0.8 Fe 0.2 O δ -SE sensor, the T 90 and T 10 were 89.9 and 321.8 s, respectively, to 50 ppm of NH 3 , while the T 90 of the BiVO 4 –SE sensor was 354.1 s.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the time required to reach 90% ΔU is defined as the response time (T 90 ), and the time required to recover to 10% ΔU is defined as the recovery time (T 10 ). 32 For the BiV 0.8 Fe 0.2 O δ -SE sensor, the T 90 and T 10 were 89.9 and 321. S5).…”
Section: ■ Experimental Sectionmentioning
confidence: 95%
“…E-strate ® is made of 3 mol% partially yttria-stabilized zirconia (3YSZ) [ 13 ]. Due to its high dielectric constant, low thermal conductivity, superior mechanical properties, and tolerance to high temperatures, E-strate ® has enabled radio frequency, photonics, chemical sensing, and renewable energy applications [ 14 , 15 , 16 , 17 ]. Various metallization techniques have been investigated on this substrate for device fabrication, while inkjet printing for device fabrication has been relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing to the metal oxide semiconductor, catalytic combustion and surface acoustic wave (SAW) gas sensors, the mixed type potential sensor has many advantages including better mechanical properties, chemical stability and thermal stability at high temperatures [9], which make mixed potential sensor work well in the harsh environment such as the automobile exhaust gas after-treatment system [8,10,11,12,13]. Recently, to further improve the performance of the mixed potential sensor effectively, many groups have turned their attention to finding more sensitive materials including single metal oxides, composite perovskite and spinel-type oxides, and also made some good results [14,15]. Researchers used In 2 O 3 as SE had reached a NO 2 response of 126 mV to 100 ppm at 700 °C [16].…”
Section: Introductionmentioning
confidence: 99%